Ազգային մոնոդիան ՂԱԶԱՐՈՍ ՍԱՐՅԱՆԻ արվեստում - Պետրոսի Զուրաբյան, Ժաննա (Musical Armenia, 2010)
Article by Professor of YSC, Ph.D. Janna Petros Zurabyan “National monody in the work of Lazar Saryan” dedicated to the theoretical analysis of the implementation by L.M. Saryan of folk song-dance “Nubar” in the suite “Symphonic Pictures” and the music for the film “Little things Provides a comparative analysis of the author’s music and folk material. The author traces the refraction of folk melodies in symphonic canvas as leit-topic in general composition.